Implementing CICS Web services - Williams, Nigel; Lopez, Luis Aused; Herman, Robert; Ebbers, Mike; Able, Grant Ward; Chieregatti, Paolo; Joergensen, Tommy; Wall, Steve (IBM Redbooks, 2007)
The Web services support in CICS Transaction Server Version 3.1 enables your CICS programs to be Web service providers or requesters. CICS supports a number of specifications including SOAP Version 1.1 and Version 1.2, and Web services distributed transactions (WS-Atomic Transaction). This IBM Redbooks publication will help you configure the CICS Web services support for both HTTP and WebSphere MQ based solutions. We show how Web services can be used to integrate J2EE applications running in WebSphere Application Server with COBOL programs running in CICS. It begins with an overview of Web services standards and the Web services support provided by CICS TS V3.1. Complete details for configuring CICS Web services using both HTTP and WebSphere MQ are provided next, along with the steps for using Web services to connect to CICS from a service integration bus. The book then shows how CICS Web services can be secured using a combination of Web Services Security (WS-Security) and transport-level security mechanisms such as SSL/TLS. Finally, it demonstrates how atomic Web services transactions can be configured to allow WebSphere and CICS resource updates to be synchronized. This book concentrates on implementation specifics such as security, transactions, and availability.
Includes indexes
Keywords: Web services; CICS (Computer system); Services Web; CICS (Système informatique)